Ciało i cielesność – ku doświadcze(a)niu egzystencjalnemu - Walczak, Anna (Humaniora. Czasopismo Internetowe, 2021)
When Emmanuel Lévinas was reflecting on the I-You relationship, he intentionally omitted the conjunction “and” to emphasise their distinctiveness and the fact that they cannot be reduced to each other. For Lévinas, the use of the conjunction “and” would indicate reciprocation – I just like You and interchangeability – I being You. However, it would also indicate such type of relationship that would be précised in the mutual dependencies – I exist thanks to You and You exist thanks to I. This could not be accepted by Lévinas, because he assumed that only I can exist due to You. Why, then, does the title of the paper contain the conjunction “and” between the body and corporeality? I assume that body and corporeality are in a relationship based on reciprocation – interdependence that is both the source (arche) and the warp of the existential experience/experiencing – what we are while becoming.